2017
DOI: 10.1111/bjh.14721
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of recurrent copy number aberrations in B‐lineage acute lymphoblastic leukaemia without recurrent fusion genes across age cohorts

Abstract: Copy number aberrations (CNAs) represent cooperating events in B-lineage acute lymphoblastic leukaemia (B-ALL); however, their clinical relevance across different age cohorts is unclear. We analysed the recurrent CNAs in 157 age-stratified B-ALL negative cases for recurrent rearrangements (B-NEG ALL), and their association with patients' clinico-biological features. We found that: (i) CDKN2A/RB1-deleted and EBF1-deleted adults had a shorter disease-free survival than those with wild-type, (ii) among the unfavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
4
17
1
Order By: Relevance
“…More concretely, CDKN2A/B deletions may represent adverse prognostic markers independent from MRD at the end of induction, indicating that testing for CDKN2A/B deletions can identify adult patients with Ph-neg BCP ALL with poor outcome, not assessable by MRD.The prognostic role of CDKN2A/B deletions has been evaluated at all ages with controversial results in BCP ALL. The impact of these deletions may be more pronounced in adults, particularly in Phpositive ALL,7 although some studies have also reported unfavorable prognosis in Ph-neg BCP-ALL 5,8. To the best of our knowledge, this is the first study reporting a prognostic significance for CDKN2A/B independent of MRD in adolescents and adults with Ph-neg BCP-ALL.…”
mentioning
confidence: 73%
“…More concretely, CDKN2A/B deletions may represent adverse prognostic markers independent from MRD at the end of induction, indicating that testing for CDKN2A/B deletions can identify adult patients with Ph-neg BCP ALL with poor outcome, not assessable by MRD.The prognostic role of CDKN2A/B deletions has been evaluated at all ages with controversial results in BCP ALL. The impact of these deletions may be more pronounced in adults, particularly in Phpositive ALL,7 although some studies have also reported unfavorable prognosis in Ph-neg BCP-ALL 5,8. To the best of our knowledge, this is the first study reporting a prognostic significance for CDKN2A/B independent of MRD in adolescents and adults with Ph-neg BCP-ALL.…”
mentioning
confidence: 73%
“…Recurrently mutated JAK/STAT and RAS pathways genes (Messina et al , ) were sequenced in 182/194 samples (Table SIV). Copy number aberrations (Messina et al , ) were assessed by multiplex ligation‐dependent probe amplification (MLPA) in 111/194 samples. RNA‐sequencing was performed in 54 samples by the TruSeq RNA Sample Preparation Kit (Illumina, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…16 IKZF1 deletions initially were recognized as a negative prognostic marker both in patients with BCR/ ABL1-positive and those with BCR/ABL1-negative ALL. 7,[45][46][47][48][49] In adult patients with BCR/ABL1-like ALL, IKZF1 deletion occurs in approximately 70% to 80% of patients. [8][9][10][11][12] IKZF1 deletions are significantly more common in patients carrying a CRLF2 rearrangement compared with patients with CRLF2 deregulation.…”
Section: Copy Number Aberrations In Patients With Bcr/ Abl1-like Allmentioning
confidence: 99%
“…Other frequently deleted genes in BCR/ABL1-like ALL are EBF1 and BTG1 (20%-40% and approximately 30% of cases, respectively), which indeed are reported to be associated with a worse outcome. [8][9][10]12,48 EBF1 deletions are enriched in cases carrying the EBF1-PDGFRB fusion due to an interstitial 5q deletion.…”
Section: Copy Number Aberrations In Patients With Bcr/ Abl1-like Allmentioning
confidence: 99%
See 1 more Smart Citation